Value Added Tax and price stability in Nigeria: A partial equilibrium analysis - Marius Ikpe; Alwell Nteegah (European Journal of Government and Economics (EJGE), 2013)
The economic impact of Value Added Tax (VAT) that was implemented in Nigeria in 1994 has generated much debate in recent times, especially with respect to its effect on the level of aggregate prices. This study empirically examines the influence of VAT on price stability in Nigeria using partial equilibrium analysis. We introduced the VAT variable in the framework of a combination of structuralist, monetarist and fiscalist approaches to inflation modelling. The analysis was carried out by applying multiple regression analysis in static form to data for the 1994-2010 period. The results reveal that VAT exerts a strong upward pressure on price levels, most likely due to the burden of VAT on intermediate outputs. The study rules out the option of VAT exemptions for intermediate outputs as a solution, due to the difficulty in distinguishing between intermediate and final outputs. Instead, it recommends a detailed post-VAT cost-benefit analysis to assess the social desirability of VAT policy in Nigeria.
Keywords: 330; Value added tax; price stability; partial equilibrium analysis; static model; Nigeria